2008
DOI: 10.4321/s0212-71992008000200003
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobinopatías diagnosticadas en el área sanitaria del Hospital Universitario Nuestra Señora de Candelaria de Santa Cruz de Tenerife durante un año

Abstract: Las hemoglobinopatías son las alteraciones monogénicas más frecuentes en el mundo y tienen un patrón de herencia autosómico recesivo. Se dividen en: hemoglobinopatías estructurales, producidas por la síntesis de una cadena de globina estructuralmente anormal, y síndromes talasémicos, que se manifiestan por la disminución total o parcial de la síntesis de una globina de estructura normal (1). INCIDENCIA Y DISTRIBUCIÓN GEOGRÁFICA La frecuencia de hemoglobinopatías en la población mundial es muy elevada y su dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…This value is three times higher than that recently reported by Modell et al with a estimated percentage of pregnant woman carriers for haemoglobinopathy of 0.34% 28. The results of a very recent haemoglobinopathy study, also performed in the Canary Islands by De Las Heras et al ,29 reported that a total of 198 haemoglobinopathies were found in an adult population, with 125 of them corresponding to structural variants. In three cases SCD was identified, and in 70 cases AS was identified.…”
Section: Scd In Spainmentioning
confidence: 58%
“…This value is three times higher than that recently reported by Modell et al with a estimated percentage of pregnant woman carriers for haemoglobinopathy of 0.34% 28. The results of a very recent haemoglobinopathy study, also performed in the Canary Islands by De Las Heras et al ,29 reported that a total of 198 haemoglobinopathies were found in an adult population, with 125 of them corresponding to structural variants. In three cases SCD was identified, and in 70 cases AS was identified.…”
Section: Scd In Spainmentioning
confidence: 58%